Learning Strategies For Listening Skills Among Arabic Learners In The Preparatory Year At Faculties Of Islamic Sciences In Turkey/ إستراتيجيات التعلم الخاصة بمهارة الاستِماع لدى متعلمي العَربيّةِ في السنة التحضيرية في كليات العلوم الإسلامية في تركيا - Mutassem Mohammad Hamad; Hammoud Younes (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Listening skills in Arabic are a gateway to acquiring knowledge and a means of learning and communication. However, many preparatory year students in the Faculties of Islamic Sciences in Turkey complain about its difficulty and suffer from weak listening skills for various reasons. Modern studies in foreign language education emphasize the necessity for learners to possess learning strategies for each language skill due to their significant importance in developing these skills and overcoming many problems and difficulties that learners may encounter. Therefore, this study aimed to explore the learning strategies specific to listening skills among Arabic learners in the preparatory year at some Turkish universities and investigate the impact of variables (gender, place of study) on their use of these strategies. The study was conducted on a sample of 127 randomly selected male and female preparatory year students nearing the end of their year at several universities for the academic year 2023-2024. To achieve the study's objectives, the researcher used the descriptive-analytical method and developed a questionnaire that included a graduated scale measuring the extent to which learners use these strategies, consisting of 20 strategies distributed across three fields: 1. Pre-listening strategies, 2. While-listening strategies, 3. post-listening strategies. The study showed that preparatory year students practice pre-listening and while-listening strategies highly, while post-listening strategies are practiced moderately. The study revealed statistically significant differences between the averages of the sample individuals attributed to gender, in favor of females, in using pre-listening and while-listening strategies, but no differences in post-listening strategies. The study also showed statistically significant differences between the averages of the sample individuals attributed to the university, with Sabahattin Zaim University ranking first, followed by Sultan Mehmet Fatih University in pre-listening and while-listening strategies. As for post-listening strategies, Sabahattin Zaim University ranked first, followed by Kocaeli University. These results emphasize the need for teachers to pay more attention to language learning strategies in all skills in their lessons, in addition to guiding their students to the correct learning strategies and training them on how to use them.